Adjustment of superconductivity and ferromagnetism in the few-layered ferromagnet-superconductor nanostructures - Izyumov, Y.A.; Khusainov, M.G.; Proshin, Y.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The phase diagrams of the few-layered nanosystems consisting of dirty superconducting (S) andferromagnetic (F) metals are investigated within the framework of the modern theory of the proximityeffect taking into account the boundary conditions. The F/S tetralayer and pentalayer are shown to have considerably richer physics than the F/S bi- and trilayer (due to the interplay between the 0 and p phase superconductivity and the 0 and p phase magnetism and nonequivalence oflayers) and even the F/S superlattices. It is proven that these systems can have different criticaltemperatures and fields for different S layers. This predicted decoupled superconductivity is found to manifest itself in its most striking way for F/S tetralayer. It is shown that F/S/F'/S' tetralayer is the most perspective candidate for use in superconducting spin nanoelectronics.